2002
DOI: 10.1021/jf011022n
|View full text |Cite
|
Sign up to set email alerts
|

Retronasal Transport of Aroma Compounds

Abstract: A comparison was made between the amounts of volatiles in the headspace above a solution and the breath volatile content (exhaled from the nose or mouth) after consumption of the same solution. The amounts of volatiles in the breath were lower than those in the headspace, with breath exhaled via the mouth containing, on average, 8-fold more volatiles than breath exhaled via the nose. Dilution of the sample by saliva in-mouth did not appear to be a major factor affecting volatile delivery. Instead, the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 18 publications
5
72
0
1
Order By: Relevance
“…Cook hypothesized, within the study, that it was the interfacial properties of the solution that are most significant in controlling flavour concentration retronasally. This was also documented by Linforth and co-workers [22] who also showed that a reduction in partition coefficient increases efficiency of volatile delivery, resulting in a volatile concentration in-nose greater than expected on a basis of K ae .…”
Section: Evaluation Of Headspace Volatile Concentration During Dynamisupporting
confidence: 66%
“…Cook hypothesized, within the study, that it was the interfacial properties of the solution that are most significant in controlling flavour concentration retronasally. This was also documented by Linforth and co-workers [22] who also showed that a reduction in partition coefficient increases efficiency of volatile delivery, resulting in a volatile concentration in-nose greater than expected on a basis of K ae .…”
Section: Evaluation Of Headspace Volatile Concentration During Dynamisupporting
confidence: 66%
“…Compounds with low K aw values were released into the breath with greater efficiency than high K aw compounds, when their in vivo release from water was compared with static headspace measurements. [13] Some of the compounds with high K aw values produced breath volatile concentration less than 5% of their headspace volatile concentration. With very low levels of volatile delivery into the breath the potential for variation is greater than when release is closer to the thermodynamic maximum.…”
Section: Resultsmentioning
confidence: 99%
“…Drinking is a short-time scale event and the volatiles do not reach an equilibrium state during the process 12 . The addition of ethanol, carbonation and hop acids could change volatile behaviour through differences in surface tension and surface creation not seen invitro.…”
Section: In-vivo Samplingmentioning
confidence: 99%